Understanding the impact of Pulsed Electric Fields treatment on the thermal and pasting properties of raw and thermally processed oat flours. (March 2020) - Duque, Sheba Mae M.; Leong, Sze Ying; Agyei, Dominic; Singh, Jaspreet; Larsen, Nigel; Oey, Indrawati
Graphical abstract: Highlights: Raw oat flour was more susceptible to PEF treatment than thermally processed one. Specific energy input was the key PEF treatment processing parameter affecting oat properties. PEF treatment caused starches to be more susceptible to gelatinisation. Oat flours showed improvement in paste stability after PEF treatment. PEF treatment enhanced retrogradation property (reduced syneresis and hardness) of raw oat flour. Abstract: The aim of this research was to investigate the effect of Pulsed Electric Fields (PEF) treatments (electric field strengths 2 and 4.4 kV/cm combined with specific energy inputs between 48 and 484 kJ/kg) on the thermal and pasting properties of oat flours. Colour, β-glucan content, particle size distribution, morphological characteristics, starch short-range molecular order, protein secondary structure, thermal, and pasting properties of raw (dehulled and milled) and thermally processed (kilned at 115 °C for 30 min and steamed at 100–104 °C for 18 min under industrial process condition) oat flours under the influence of PEF treatment were evaluated. Results showed that PEF treatment, applied at any intensity, led to considerable changes in the structural properties especially when applied on raw oat flour. Both types of oat flour experienced an increase in particle size (up to four-fold), damage of starch granule morphology, and modifications in starch short-range molecular order and protein secondary structures as a result of PEF treatment. These physical changes observed after PEF treatment, particularly at increasing specific energy input, coincided with the thermal and pasting behaviour of PEF-treated oat flours, which include a decrease in gelatinisation enthalpy (up to 80%), increase in thermal transition temperatures (at least 3 °C), decrease in overall viscosity profile, and reduction in pasting temperature (up to 12 °C). Overall results suggested that PEF treatment improved majorly on starch-related functionality of oat, such as increased the pasting stability of raw and thermally processed oat flours and at the same time enhanced the retrogradation property (reduced syneresis and hardness) of raw oat flour, under lower temperature requirement without affecting pasting time. This research demonstrated the potential of PEF treatment in modifying the thermal and pasting properties of oat flour, thereby offering opportunities for novel products for food industry.